Urban Spatial Management and Planning Based on the Interactions Between Ecosystem Services: A Case Study of the Beijing–Tianjin–Hebei Urban Agglomeration - Yue Hu; Xixi Xu; Xuening Huang; Ying Li; Jiaxi Cao; Yimeng Yan; Xiaodan Hu; Shuhong Wu (Remote Sensing)
Understanding the intricate relationships among ecosystem services (ESs) and clarifying their driving factors are essential prerequisites for establishing effective ecosystem management strategies. Therefore, we plotted the spatial-temporal distribution of five ESs in the Beijing-Tianjin-Hebei (BTH) urban agglomeration and analyzed their interactions in terms of trade-offs, synergies, and bundles. We identified the primary drivers impacting ESs and proposed recommendations for urban spatial management and planning. The result revealed that (1) between 2000 and 2020, the supply of soil conservation increased the most, by 52.56%, and habitat quality decreased the most, by 6.92%; (2) four ES pairs were synergies and six ES pairs exhibited trade-offs, with three ES pairs showing decreased synergies and two ES pairs showing increased trade-offs; (3) the main factors influencing the driving forces of ESs were precipitation, cropland area ratio, and forest area ratio; and (4) the spatial-temporal analysis of ES interactions determined that ESs exhibiting decreasing synergies should be prioritized in ecosystem management, suggesting that the spatial planning of ecosystems should be based on ES bundles. Thus, this study provides guidance for regional ecosystem spatial planning and management.